1962
DOI: 10.1029/jz067i004p01437
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the scour resistance of cohesive sediments

Abstract: Previous studies of the scour of cohesive materials as presented in engineering literature and as obtained directly by personal contact are briefly reviewed. Exploratory tests for measuring scour resistance are described, and some correlated results are presented for a test involving scour by a vertical submerged jet impinging on the horizontal surface of a soil sample. The characteristics of the scour surface were observed for a remolded and a natural sediment, and the rates of scour were measured by the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(35 citation statements)
references
References 1 publication
2
32
0
1
Order By: Relevance
“…The first two refer to a critical point for initiating erosion in cohesive substrates, which Dunn (1959) reported to be definite and reproducible in clay samples. The present observations support Moore and Masch (1962) who unlike Dunn found that some sediments required a greater force to cause incipient scour than was needed to continue subsequent erosion. It would be interesting to have more data on the microbial status of the test sediments in each case.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…The first two refer to a critical point for initiating erosion in cohesive substrates, which Dunn (1959) reported to be definite and reproducible in clay samples. The present observations support Moore and Masch (1962) who unlike Dunn found that some sediments required a greater force to cause incipient scour than was needed to continue subsequent erosion. It would be interesting to have more data on the microbial status of the test sediments in each case.…”
supporting
confidence: 80%
“…The use of a submerged perpendicular jet to measure the resistance of cohesive sediment to erosion is not new (Dunn 1959;Moore and Masch 1962). The importance of the present study is its adaptation to measure short-term changes in sediment stability.…”
mentioning
confidence: 99%
See 3 more Smart Citations